2016
DOI: 10.1007/s40094-016-0226-8
|View full text |Cite
|
Sign up to set email alerts
|

A study on dust acoustic traveling wave solutions and quasiperiodic route to chaos in nonthermal magnetoplasmas

Abstract: Bifurcations and chaotic behaviors of dust acoustic traveling waves in magnetoplasmas with nonthermal ions featuring Cairns-Tsallis distribution is investigated on the framework of the further modified Kadomtsev-Petviashili (FMKP) equation. The FMKP equation is derived employing the reductive perturbation technique (RPT). Bifurcations of dust acoustic traveling waves of the FMKP equation is presented. Using the bifurcation theory of planar dynamical systems, two new analytical traveling wave solutions for soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…A soliton solution of Equation (88) corresponds to the homoclinic orbit, which is formed around the saddle point, while periodic orbits will be formed around the centre point, which gives nonlinear periodic travelling wave solution. [ 30,38,40 ]…”
Section: Phase Portrait and Chaos Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A soliton solution of Equation (88) corresponds to the homoclinic orbit, which is formed around the saddle point, while periodic orbits will be formed around the centre point, which gives nonlinear periodic travelling wave solution. [ 30,38,40 ]…”
Section: Phase Portrait and Chaos Analysismentioning
confidence: 99%
“…[ 37 ] The dust acoustic travelling wave solution and quasiperiodic route to chaos in nonthermal magnetoplasma have been investigated. [ 38 ] The nonlinear dynamical study of ion acoustic wave in a quantum pair plasma has also been done by controlling parameters such as quantum parameter and variations of the Mach number. [ 39 ] Recently, the dynamical properties of the nonlinear Schrödinger equation have been investigated for ion acoustic waves in a quantum plasma.…”
Section: Introductionmentioning
confidence: 99%
“…El‐Tantawy et al [ 37 ] have applied the hybrid distribution function to investigate the head‐on collision of ion acoustic solitons and rogue waves. The study of DAW and dust ion acoustic waves have also been performed with electrons featuring the hybrid Cairns–Tsallis distribution by Saha et al [ 38 ] and Guo and Mei, [ 39 ] respectively. Recently, several theoretical investigations [ 40–45 ] have been performed in different plasma models for electrostatic and electromagnetic waves by adopting the hybrid Cairns–Tsallis velocity distribution for lighter particles.…”
Section: Introductionmentioning
confidence: 99%
“…[8] showed that the presence of a non-Maxwellian distribution of electrons could trans…gure the nature of nonlinear density excitations to allow for the existence of structures observed by the Freja and Viking satellites [9], [10]. Various studies have shown that the non-Maxwellian distributions signi…cantly modify the linear and nonlinear propagation of waves in plasmas [11], [12], [13]. [15], [16].…”
Section: Introductionmentioning
confidence: 99%